Environment and Varroa destructor management as determinant of colony losses in apiaries under temperate and subtropical climate - Molineri, Ana Ines; Giacobino, Agostina; Pacini, Adriana Cecilia; Bulacio Cagnolo, Natalia Veronica; Merke, Julieta; Orellano, Emanuel; Bertozzi, Ezequiel; Zago, Luis Fernando Basili; Aignasse, Andrea María Elisa; Pietronave, Hernan Pablo; Rodriguez, Graciela Adriana; Crisanti, Paola Andrea; et al. (2018)
For the last 10 years, honey bee colony losses have been a topic of interest for researchers around the world, and many drivers for losses were described. The aim of this study was to evaluate the risk factors associated with annual colony losses in apiaries located in regions under subtropical and temperate climate from Argentina. In order to accomplish this, a series of three face-to-face interviews with beekeepers were carried out and samples for pathogens determination were taken from February to October 2015, in North-Central Argentina. A total of 69 apiaries were included in the study. We found that apiaries with high Varroa infestation level before treatment were more likely to suffer higher mortality rates and those beekeepers who used illegal or homemade products (or those that are legal but are not applied according to label instructions) to treat varroa, had more probabilities of having higher losses rate than those who did not treat them at all. Also, migratory beekeepers had higher total losses rate than stationary ones. The eco-regions where the apiaries were located also had differences in their mortality rates indicating a location effect. In the spatial analysis of the losses, six significant clusters with low and high mortality rates were detected within the geographical range. The colony losses rate is a multifactorial outcome, where the environment and the management practices interact in a complex way. Regions that are environmentally suitable for beekeeping can tolerate poor management practices. On the other hand, regions where beekeeping and agriculture share the same area require more careful management to keep colony losses under control.